Plant Rhizosphere Selection of Plasmodiophorid Lineages from Bulk Soil: The Importance of “Hidden” Diversity - Bass, David; van der Gast, Christopher; Thomson, Serena; Neuhauser, Sigrid; Hilton, Sally; Bending, Gary D. (Frontiers in Microbiology, 2018)
Microbial communities closely associated with the rhizosphere can have strong positive and negative impacts on plant health and growth. We used a group-specific amplicon approach to investigate local scale drivers in the diversity and distribution of plasmodiophorids in rhizosphere/root and bulk soil samples from oilseed rape (OSR) and wheat agri-systems. Plasmodiophorids are plant- and stramenopile-associated protists including well known plant pathogens as well as symptomless endobiotic species. We detected 28 plasmodiophorid lineages (OTUs), many of them novel, and showed that plasmodiophorid communities were highly dissimilar and significantly divergent between wheat and OSR rhizospheres and between rhizosphere and bulk soil samples. Bulk soil communities were not significantly different between OSR and wheat systems. Wheat and OSR rhizospheres selected for different plasmodiophorid lineages. An OTU corresponding to Spongospora nasturtii was positively selected in the OSR rhizosphere, as were two genetically distinct OTUs. Two novel lineages related to Sorosphaerula veronicae were significantly associated with wheat rhizosphere samples, indicating unknown plant-protist relationships. We show that group-targeted eDNA approaches to microbial symbiont-host ecology reveal significant novel diversity and enable inference of differential activity and potential interactions between sequence types, as well as their presence.